Mockup-Driven Development: Providing agile support for Model-Driven Web Engineering - Rivero, José Matías; Grigera, Julián; Rossi, Gustavo; Robles Luna, Esteban; Montero, Francisco; Gaedke, Martin (Information and software technology, 2014)
Agile software development approaches are currently becoming the industry standard for Web Application development. On the other hand, Model-Driven Web Engineering (MDWE) methodologies are known to improve productivity when building this kind of applications. However, current MDWE methodologies tend to ignore important aspects of Web Applications development supported by agile processes, such as constant customer feedback or early design of user interfaces. In this paper we analyze the difficulties of supporting agile features in MDWE methodologies. Then, we propose an approach that eases the incorporation of well-known agile practices to MDWE. We propose using User Interface prototypes (usually known as mockups) as a way to start the modeling process in the context of a mixed agile-MDWE process. To assist this process, we defined a lightweight metamodel that allows modeling features over mockups, interacting with end-users and generating MDWE models. Then, we conducted a statistical evaluation of both approaches (traditional vs. mockup-based modeling). First we comment on how agile features can be added to MDWE processes using mockups. Then, we show by means of a quantitative study that the proposed approach is faster, less error-prone and still as complete as traditional MDWE processes. The use of mockups to guide the MDWE process helps in the reduction of the development cycle as well as in the incorporation of agile practices in the model-driven workflow. Complete MDWE models can be built and generated by using lightweight modeling over User Interface mockups, and this process suggests being more efficient, in terms of errors and effort, than traditional modeling in MDWE.